2015
DOI: 10.1093/cercor/bhv274
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Either Rac1 or Rac3 GTPase Differentially Affects the Behavior of Mutant Mice and the Development of Functional GABAergic Networks

Abstract: Rac GTPases regulate the development of cortical/hippocampal GABAergic interneurons by affecting the early development and migration of GABAergic precursors. We have addressed the function of Rac1 and Rac3 proteins during the late maturation of hippocampal interneurons. We observed specific phenotypic differences between conditional Rac1 and full Rac3 knockout mice. Rac1 deletion caused greater generalized hyperactivity and cognitive impairment compared with Rac3 deletion. This phenotype matched with a more ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…In this direction, we have addressed the role of Rac GTPases in the development of these cells. Based on recent findings that Rac's are essential players for the correct development of cortical and hippocampal GABAergic cells in vivo (Vaghi et al, 2014; Tivodar et al, 2015; Pennucci et al, 2016), we have confirmed here that depletion of the endogenous Rac‘s impairs the neuritogenesis of interneurons in vitro .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In this direction, we have addressed the role of Rac GTPases in the development of these cells. Based on recent findings that Rac's are essential players for the correct development of cortical and hippocampal GABAergic cells in vivo (Vaghi et al, 2014; Tivodar et al, 2015; Pennucci et al, 2016), we have confirmed here that depletion of the endogenous Rac‘s impairs the neuritogenesis of interneurons in vitro .…”
Section: Discussionsupporting
confidence: 86%
“…Our previous works has shown that Rac1 represented approximately 92% and Rac3 8% of total Rac proteins in P7 mouse brain (Corbetta et al, 2009). Analysis in vivo has shown that single and double Rac knockout affects the development of cortical and hippocampal interneurons (Vaghi et al, 2014; Tivodar et al, 2015; Pennucci et al, 2016). Here we have tested the effects of Rac deletion on the maturation of MGE-derived interneurons in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rac1 is a member of the Ras superfamily of Rho proteins, and it plays an essential role in many cellular processes, including mitogenesis, kinase cascade activation, transcriptional activation, DNA synthesis and cytoskeleton reorganization [37][38][39][40][41][42]. Rac1 overexpression has been found in various types of cancer, such as lung cancer, gastric cancer, pancreatic cancer, bladder cancer and breast cancer [43][44][45][46][47].…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…In addition, it is important to note that apart from genetic defects, many other types of manipulations have been used to show that a vast array of early developmental challenges result in profuse long-term neural and cognitive effects (such as on dendritic spine density, brain volume, and attention and working memory) that last well into adulthood; when delayed or presented in adulthood, similar manipulations have less pronounced effect. Such manipulations include brain insults during gestation, parturition or the early postnatal period, as well as altered maternal care and post-weaning isolation, maternal malnutrition and vitamins deficiencies, or early pharmacological treatments (Cope et al, 2016a;Cope et al, 2016b;Lipska et al, 2002a;Lipska et al, 2002b;Lipska et al, 1992;Lipska et al, 2001;Pennucci et al, 2016).…”
Section: The Importance Of Assessing Developmental Trajectoriesmentioning
confidence: 99%